Actinic Prurigo in Singaporean Chinese: A Positive Association with HLA‐DRB1*03:01. (11th February 2016) - Chen, Qiping; Shen, Meixin; Heng, Yee Kiat; Theng, Thiam Seng Colin; Tey, Hong Liang; Ren, Ee Chee; Chong, Wei‐Sheng
Abstract: Studies have reported the association of human leukocyte antigen (HLA) genes with susceptibility to develop actinic prurigo (AP) in Caucasians, but there were no studies in Asian populations, including the Chinese. Our study was performed to determine if AP is associated with susceptibility or protective HLA alleles or haplotypes in Singaporean Chinese. All Chinese patients diagnosed with AP at National Skin Center, Singapore, from January 2002 to April 2015 were invited to participate in the study. Clinical data and phototesting results were collated, and HLA typing was performed. Among 14 patients included, 11 were male and the mean age was 49.6 (37.9–61.3) years. All patients did not have a family history of AP and none had mucosal involvement, as such these clinical features differed from Caucasian AP patients. The frequency of DRB1*03:01 in AP patients was significantly higher compared to healthy controls (43% vs 16%, P = 0.022, odds ratio (OR) 3.89). Concurrently, the frequency of HLA‐B*58:01‐DRB1*03:01 haplotype was also significantly increased (25% vs 7%, P = 0.004, OR 4.23). In conclusion, HLA‐DRB1*03:01 was associated with AP in Singaporean Chinese patients. This novel allelic association may possibly be utilized as a biological marker to aid in the diagnosis of AP in Chinese patients. Abstract : Studies have reported the association of human leukocyte antigen (HLA) genes with susceptibility to develop actinic prurigo (AP) in Caucasians, but there were no studies in Asian populations, including the Chinese. Our study was performed to determine if AP is associated with susceptibility or protective HLA alleles or haplotypes in Singaporean Chinese. We found that HLA‐DRB1*03:01 was associated with AP in Singaporean Chinese patients. This novel allelic association may possibly be utilized as a biological marker to aid in the diagnosis of AP in Chinese patients.